Analisa Tebal dan Perpanjangan Landasan Pacu pada Bandar Udara Internasional Sultan Mahmud Badaruddin II - Hastha Yuda Pratama (Jurnal Teknik Sipil dan Lingkungan, 2015)
In South Sumatra, especially in Palembang, total passengers of air transport increased annually. The infrastructure of airfield must be improved, the needed of extension of landing and take-off area aircraft. This research includes the "Analysis of Thickness and Extension of Runway at The International Airport of Sultan Mahmud Badaruddin II". Ability of runway can serve the maximum aircraft type is the Airbus 320. Based on the the calculation results, the length of corrected Runway 11 is 3828 m and the length of corrected Runway 29 is 3822 m. From the data has been analyzed, pavement thickness with graphic using the FAA method, a thickness of surface layer is 12.7 cm, a thickness of base layer is 12.7 cm, and a thickness of subbase layer is 58.42 cm. While, the pavement thickness with analytical using the CBR method, a thickness of surface layer (asphalt) is 10 cm, a thickness of base layer (crush stone base) is 21 cm, and a thickness of gravel subbase layer is 53 cm. In the analysis, the total of aircraft movements per year in 2017 is 34022. The total of aircraft movements per month in 2017 are January 2758, February 2774, March 2789, April 2804, May 2819, June 2835, July 2850, August 2865, September 2881, October 2896, November 2911, and December 2927.Key Words : length of corrected runway, pavement thickness, total of aircraft movements, runway